Identification of 22q11.2 deletion syndrome via newborn screening for severe combined immunodeficiency. Two years' experience in Catalonia (Spain). Issue 12 (30th October 2019) - Martin‐Nalda, Andrea; Cueto‐González, Anna M.; Argudo‐Ramírez, Ana; Marin‐Soria, Jose L.; Martinez‐Gallo, Monica; Colobran, Roger; Plaja, Albert; Castells, Neus; Riviere, Jacques; Tizzano, Eduardo F.; Soler‐Palacin, Pere
Abstract: Background: The current scenario of newborn screening is changing as DNA studies are being included in the programs of several countries. Severe combined immunodeficiency (SCID) disorders can be detected using quantitative PCR assays to measure T‐cell receptor excision circles (TRECs), a byproduct of correct T‐cell development. However, in addition to SCID, other T‐cell‐deficient phenotypes such as 22q11.2 deletion syndrome 22q11.2 duplication syndrome, CHARGE syndrome, and trisomy 21 are detected. Methods: We present our experience with the detection of 22q11.2 deletion syndrome and 22q11.2 duplication syndrome in a series of 103, 903 newborns included in the newborn screening program of Catalonia (Spain). Results: Thirty newborns tested were positive (low TREC levels) and five were found to have copy number variations at the 22q11 region (4 deletions and 1 duplication) when investigated with array comparative genomic hybridization technology and MLPA. Conclusion: Newborn screening for SCID enables detection of several conditions, such as 22q syndromes, which should be managed by prompt, proactive approaches with adequate counseling for families by a multidisciplinary team. Abstract : Newborn screening (NBS) using T‐cell receptor excision circle (TREC) assays to detect severe combined immunodeficiency (SCID) has been established in several geographic areas. In addition to SCID, other T‐cell deficient conditions, such as 22q11.2 deletion syndrome (DS), CHARGE syndrome, and trisomy 21, can also be detected through NBS. An early diagnosis of 22q11.2 DS is associated with a better clinical outcome, mainly because of the possibility of early protocolled care, including rehabilitation and adapted school programs, an appropriate vaccination schedule, and adequate genetic counseling.